Pengaruh Tingkat Inflasi, Profitabilitas, Leverage, Dan Perencanaan Pajak Terhadap Return Saham (Studi Pada Perusahaan Real Estate Dan Property Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2017) - Ayem, Sri; Nurasjati, Pratiwi (AKMENIKA, 2020)
The purpose of this study was to determine the effect of inflation, profitability, leverage, and tax planning on stock returns. This research includes descriptive research. The population in this study are property and real estate companies that are listed on the Indonesia Stock Exchange for the period 2014-2017. The sample in this study was determined by purposive sampling method and obtained 28 companies, samples within the period of 4 years of annual financial statements. The type of data used is secondary data. To determine the effect of independent variables with the dependent variable using the method of multiple regression analysis. The results of this study are that the inflation rate has a significant positive effect, profitability has a significant positive effect, leverage has no effect, and tax planning has no effect on stock returns Keywords: Inflation Rate, Profitability, Leverage, Tax Planning, and Stock Return